Addressing education and training needs of road safety auditors. Issue 1 (1st January 2018) - Vardaki, Sophia; Bekiaris, Evangelos; Kanellaidis, George
Abstract: According to national (Greek) and European legislation on road infrastructure safety management, road safety auditing is mandatory for the Trans-European Road Network. This paper presents the development of a training course and educational material for candidate road safety auditors in Greece, aiming to adequately prepare them to conduct road safety audits. In particular, the principles upon which the road safety audit training course is based, the learning objectives, the course outline and the proposed framework of the curriculum are presented. The training course takes into consideration recent developments in road safety, as well as local conditions and needs. Because it places emphasis on the implementation of the Safe System and human factors in road design, it may contribute to the development of a positive safety culture among highway professionals involved in the road design and road operation process. The process of its development may be regarded as a proposal for good practice for the development of professional development training programmes, addressing the relevant training needs and achieving the relevant training objectives.